EFFECTS OF APPLYING PROTECTION MOTIVATION THEORY ON PREVENTION BEHAVIOR OF THE CORONAVIRUS DISEASE 2019 AMONG VILLAGE HEALTH VOLUNTEER IN LAO DAENG SUB-DISTRICT, DON MOT DAENG DISTRICT, UBON RATCHATHANI PROVINCE - สุหงษา นันทภัค (Primary Health Care Journal (Northeastern Edition), 2023)
The purpose of this quasi – experimental research was to study the effects of the program of applying protection with behaviors prevention of Coronavirus Disease 2019 among village health volunteers, Lao Daeng Sub-district, Don Mod Daeng District, Ubon Ratchathani Province. The experimental group consisted of 33 participate group was received a health prevention program. The control group consisted of 33non received regular health prevention program by purposive sampling. The instrument was health prevention coronavirus disease 2019program and questionnaire by researcher. The Cranach’s alpha coefficient of scores of 0.75 Percentage, mean, standard deviation and independent samples t-test were applied for data analysis. The results of this study were as follows: After receiving the village health volunteers program the experimental group had the average knowledge score. perception of violence perceived opportunities, risks, expectations, self-efficacy and had better preventive behaviors against the novel coronavirus 2019 than the control group statistically significant at .01.